Technologist-Historian. - SHELL, HANNA ROSE; WELLERSTEIN, ALEX (Technology & Culture, 2015)
An interview is presented with Alex Wellerstein, professor of Science and Technology Studies at the Stevens Institute of Technology, focusing on NukeMap, an interactive online data-visualization tool that allows users to see the impact that various nuclear weapons would have if detonated at different global locations. Topics include why he revised the original two-dimensional version to make it three-dimensional, historical aspects of the project, and how it has been used in college courses.